ANALISIS KESALAHAN SISWA KELAS VII MTs ALKHAIRAAT PUSAT PALU DALAM MENYELESAIKAN SOAL BENTUK ALJABAR BERDASARKAN PROSEDUR NEWMAN - Nurwahyuni Biringkanae; I Nyoman Murdiana; Nurhayadi Nurhayadi (Universitas Tadulako, 2025)
This study is a qualitative research that aims to obtain a description of the types of errors and factors that cause errors made by seventh grade students of MTs Alkhairaat Pusat Palu in solving algebraic form problems using error analysis based on the Newman Procedure. This data was collected through written tests and interviews. The subject of this study was one student of class VII C at MTs Alkhairaat Pusat Palu who made the most mistakes. The results of this study indicate that the types of errors made by students are: (1) Reading errors, namely students cannot read the symbols contained in the problem; (2)Comprehension errors, namely students misunderstand the problem in the problem; (3) Transformation errors, namely students incorrectly determine the solution steps to be used in solving the problem; (4) Process skill errors, namely students incorrectly calculate the results of subtraction; and (5) Encoding errors, namely students incorrect in writing the final answer. The factors that cause errors made by students are: (1) students do not know the symbols in the problem; (2) lack of understanding of algebraic form material; (3) do not know the correct steps in solving the problem; (4) do not apply the concept of arithmetic operations correctly; and (5) lack of thoroughness and rush when solving the problem.